Bucking the current trend in bioelectrochemical systems: a case for bioelectroanalytics. (19th May 2018) - Seviour, Thomas William; Hinks, Jamie
Abstract: Turning wastewater directly into electricity is alluring, widespread use of microbial fuel cells (MFCs) to achieve this at industrial scale appears increasingly unlikely despite intense research efforts lasting over a decade. Such endeavors have not been futile, however, and game-changing discoveries have resulted from these well-intentioned, scientifically rigorous but ultimately frustrated attempts to resolve the Waste-Energy dichotomy. The appeal of MFCs is largely of conceptual elegance rather than financial competitiveness, based on the green ideal that bacteria can be turned into cost effective bio-batteries. This notion is founded on the solid principles of extracellular electron transfer (EET), where microbes use electrodes interchangeably with other electron acceptors to generate current as a direct proxy for microbial metabolism. We contend that a nuanced understanding of EET has been restricted by focusing on device performance when in fact this information could be more beneficially channeled into addressing analytical questions pertaining to the presence and activity of microorganisms across systems of environmental and medical import, i.e. bioelectroanalytics. We discuss here relevant literature detailing bioelectrochemical systems and contrast energy-centric conclusions with observations geared towards bioelectroanalytics. We explore the expanding possibilities of bioelectroanalytics enabled by advances in genetic techniques and rooted in the concept that microbial interactions with an electrode extend to more than just cells seeking alternative electron acceptors. Our intention is to highlight alternative directions in the field and encourage researchers to harness bioelectroanalytics to address wider societal problems, in addition to addressing climate change.